Neighbourhood deprivation and quality of comprehensive diabetes care: findings from a national retrospective cohort study of US Medicare Advantage enrollees - Leonor Corsino; Bradley G Hammill; Beau Blass; Jay B Lusk; Hannah Mahoney; Amy G Clark (BMJ Open)
Objective This study aims to assess the association between neighbourhood socioeconomic deprivation and outcomes reflecting comprehensive diabetes care (CDC).Design Retrospective cohort studySetting US Medicare Advantage (MA) data, 2015–2020.Participants National sample of MA enrollees with diabetes.Outcome measures Primary outcomes included six indicators of CDC from the Healthcare Effectiveness Data and Information Set: haemoglobin (Hb) A1c (HbA1c) testing, HbA1c control (<8%), HbA1c poor control (>9%), blood pressure control (<140/90 mm Hg), receipt of eye exams and medical attention for nephropathy.Results There were 827 227 enrolments included in the final analysis. After adjusting for demographic (age, sex, race/ethnicity and dual eligibility) and regional characteristics (rurality and primary care providers per capita), high neighbourhood deprivation was associated only with worse glycaemic control (for HbA1c>9%, risk ratio (RR) 1.04, 95% CI 1.02 to 1.07). This relationship was significant for white and Asian patients (RR 1.08, 95% CI 1.05 to 1.11 and RR 1.18, 95% CI 1.05 to 1.32, respectively); outcomes for black and Hispanic patients were worse overall but independent of neighbourhood deprivation (RR 1.00, 95% CI 0.96 to 1.05 and RR 0.98, 95% CI 0.94 to 1.03, respectively). In the fully adjusted model, neighbourhood deprivation was not associated with measures that directly reflect access to care, including the occurrence of HbA1c testing and receipt of eye exams (RR 0.99, 95% CI 0.94 to 1.04 and RR 1.03, 95% CI 1.00 to 1.05).Conclusions An increased risk of poor glycaemic control was observed for patients from areas of high neighbourhood deprivation, independent of individual socioeconomic status. Neighbourhood factors and their intersection with racial and ethnic disparities are important considerations for achieving equity in diabetes care.